Sublethal ciprofloxacin treatment leads to resistance via antioxidant systems in Proteus mirabilis - Aiassa, Virginia (2012)
This study investigates new aspects of the possible role of antioxidant defenses in the mechanisms of resistance to ciprofloxacin in Proteus mirabilis. Four ciprofloxacin-resistant variants (CRVs), selected in vitro by repeated cultures in a subminimum inhibitory concentration (MIC) concentration of ciprofloxacin, attained different levels of antibiotic resistance and high Ferric reducing antioxidant power, with 10 6 frequencies. However, no mutations occurred in positions 83 or 87 of gyrA, 464 or 466 of gyrB, or 78, 80 or 84 of parC, suggesting that resistance took place without these typical mutations in DNA gyrase or topoisomerase IV. Assays with ciprofloxacin and the pump inhibitor carbonyl cyanide m-chlorophenylhydrazone showed that in addition to the antioxidant mechanisms, the influx/efflux mechanism also contributed to the increase in the resistance to ciprofloxacin in one CRV. Moreover, lipid oxidation to malondialdehyde and protein oxidation to carbonyls and advanced oxidation protein products were higher in sensitive than in the resistant strains, as a new factor involved in the mechanisms of resistance in P. mirabilis. The oxidative stress cross-resistance to telluride in CRVs enhanced the role of the antioxidants in the ciprofloxacin resistance of P. mirabilis, which was reinforced during the assays of reduction of susceptibility to ciprofloxacin by glutathione and ascorbic acid.